Cardioprotective effect of preconditioning is more efficient than postconditioning in rats submitted to cardiac ischemia and reperfusion - Tavares,José Gustavo Padrão (2018)
Abstract Purpose: To investigate the cardioprotective effects of ischemic preconditioning (preIC) and postconditioning (postIC) in animal model of cardiac ischemia/reperfusion. Methods: Adult rats were submitted to protocol of cardiac ischemia/reperfusion (I/R) and randomized into three experimental groups: cardiac I/R (n=33), preCI + cardiac I/R (n=7) and postCI + cardiac I/R (n=8). After this I/R protocol, the incidence of ventricular arrhythmia (VA), atrioventricular block (AVB) and lethality (LET) was evaluated using the electrocardiogram (ECG) analysis. Results: After reestablishment of coronary blood flow, we observed variations of the ECG trace with increased incidence of ventricular arrhythmia (VA) (85%), atrioventricular block (AVB) (79%), and increase of lethality (70%) in cardiac I/R group. The comparison between I/R + preIC group with I/R group demonstrated significant reduction in VA incidence to 28%, AVB to 0% and lethality to 14%. The comparison of I/R + postIC group with I/R group was observed significance reduction in AVB incidence to 25% and lethality to 25%. Conclusion: The preconditioning strategies produce cardioprotection more efficient that postconditioning against myocardial dysfunctions and lethality by cardiac ischemia and reperfusion.